1955
DOI: 10.1099/00221287-12-2-311
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Microflora of the Clothes Moth Larva Tineola bisselliella in relation to Wool Digestion

Abstract: SUMMARY:The intestines of clothes moth larvae, Tineola bisselliella, examined usually contained very few micro-organisms; this may be related to the high pH values of the intestinal contents. It was concluded that bacteria play no part in the digestion of wool by these larvae.It was shown by Linderstram-Lang & Duspiva (1936) and by Waterhouse (1952) that the mid-gut of the clothes moth larva, Tineola bisselliella, has a reduction potential of c. -250 mV. at pH values near 10. These reducing conditions, though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1962
1962
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…An alternative explanation for the adaptation of the clothing moth to keratin-based diets is that keratinase activity is conferred by specific bacterial symbionts in the gut. Although previous studies found no abundant microorganisms in T. bisselliella larvae [21,22], we were able to reproducibly isolate bacteria from the midgut of larvae fed on a feather diet. Most of the isolates were identified as Clostridiales, Lactobacillales, and the genus Bacillus, similar to the bacteria associated with the brown house moth Hofmannophila pseudospretella, another keratin-feeding lepidopteran [23].…”
Section: Discussionmentioning
confidence: 69%
“…An alternative explanation for the adaptation of the clothing moth to keratin-based diets is that keratinase activity is conferred by specific bacterial symbionts in the gut. Although previous studies found no abundant microorganisms in T. bisselliella larvae [21,22], we were able to reproducibly isolate bacteria from the midgut of larvae fed on a feather diet. Most of the isolates were identified as Clostridiales, Lactobacillales, and the genus Bacillus, similar to the bacteria associated with the brown house moth Hofmannophila pseudospretella, another keratin-feeding lepidopteran [23].…”
Section: Discussionmentioning
confidence: 69%
“…Since keratinases are only known from bacteria and fungi ( Hughes and Vogler, 2006 ), it is possible that a microbial partner is involved in this digestion. Despite this, the mechanism by which T. bisselliella uses keratin is yet to be clarified, firstly because Crewther and Mcquade (1955) did not find any culturable bacterial colonies in the gut that could play this role, and secondly because the complete microbiome of this species has not been characterized. In addition, genes that resemble bacterial sequences encoding keratinolytic enzymes were not found in the genome of this moth in a later study ( Hughes and Vogler, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many insects are known to have micro‐organisms in the gut which can play a role in nutrition (Slansky and Rodriguez 1987). However, studies on the keratinophagous larva of Tineola bisselliella (Lepidoptera, Tineidae) found no evidence for the presence of micro‐organisms in the midgut (Crewther and McQuade 1955; Kasper 1978) other than a single specimen infected with a microsporidium.…”
Section: Introductionmentioning
confidence: 99%